TINJAUAN BLACK SPOT JALAN NASIONAL LINTAS TIMUR PROVINSI ACEH - Herman Herman; Sofyan M. Saleh; Renni Anggraini (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2016)
Abstract: The existence of national road status in east coast of Aceh Province plays important role in triggering evonomic growth in Aceh. However, there are myriads of challenges especially in North Aceh District corridor that somehow caused traffic accident. This study aimed to determine the characteristics and causes of traffic accidents by identifying and analyzing the treatment to reduce traffic accidents. The study was conducted on national road in East Coast Aceh Province traffic approximately near Kr. Mane bend, bend of Iskandar Muda Fertilizer company, and bend of Panton Labu Bridge. Results showed that the geometrical condition round the corner of Kr. Mane has type 2 lanes 2-way street which is undivided (2/2 UD) with a lane width of 2.0 x 3.5 m and shoulders width of 2.0 m. The cause of traffic accidents identified succesfully near the curve with a small radius. Furthermore, around the corner of the two roads into the village there are no such traffic lights and the distance of the poor in a corner because of some planted trees. Meanwhile, the bend of Iskandar Muda Fertilizer company has type 2 lanes 2-way street which is undivided (2/2 UD) with a lane width of 2.0 x 8.0 m and shoulders width of 0.5 m The cause of traffic accidents identified succesfully near the corner of the railway bridge and highway bridges. Additionally, lack of or lack of traffic signs and bend their driveway the village, and there are no traffic lights completed the traffice accident factors. Lastly, the corner of Panton Labu Bridge type of road has type 2 lanes 2-way street which is undivided (2/2 UD) with a lane width of 2.0 x 3.8 m and shoulders width of 2.0 m and the causes of traffic accidents is poor visibility on bends, the building closest to the road, 800 m from the intersection there is a bridge frame, the head of the bridge is only 20 m from the bend, the entrance to the village, banners attract attention and distract the driver, the vehicle parked haphazardly. This research is expected to provide information about the location of the accident-prone spots to reduce the risk of accidents.Keywords : traffic, accidents, geometric, bend, black spotAbstrak: Jalan nasional pada lintas timur memiliki nilai yang sangat strategis dalam mendukung perkembangan dan pertumbuhan ekonomi di Provinsi Aceh. Pada jalan nasional lintas timur di Kabupaten Aceh Utara terdapat beberapa lokasi yang menjadi lokasi titik rawan kecelakaan. Penelitian dilakukan pada ruas jalan nasional lintas timur yaitu pada tikungan Kr. Mane, tikungan depan Perusahaan Pupuk Iskandar Muda, tikungan Jembatan Panton Labu. Hasil dari penelitian bahwa kondisi geometrik di tikungan Kr. Mane mempunyai tipe jalan 2 lajur 2 arah tidak terbagi (2/2 UD) dengan lebar lajur 2,0 x 3,5 m dan lebar bahu 2,0 m dan faktor penyebab terjadinya kecelakaan lalu lintas yaitu adanya tikungan dengan radius kecil, di tikungan adanya dua jalan masuk ke desa, tidak ada lampu jalan dan jarak pandang buruk pada tikungan karena adanya pepohonan. Tikungan depan Perusahaan Pupuk Iskandar Muda mempunyai tipe jalan 2 lajur 2 arah tidak terbagi (2/2 UD) dengan lebar lajur 2,0 x 8,0 m dan lebar bahu 0,5 m dan faktor penyebab terjadinya kecelakaan lalu lintas yaitu tikungan dekat jembatan kereta api dan jembatan jalan raya, kurang atau minimnya rambu lalu lintas dan di tikungan adanya jalan masuk ke desa, dan tidak ada lampu jalan. Tikungan Jembatan Panton Labu mempunyai tipe jalan 2 lajur 2 arah tidak terbagi (2/2 UD) dengan lebar lajur 2,0 x 3,8 m dan lebar bahu 2,0 m dan faktor penyebab terjadinya kecelakaan lalu lintas yaitu jarak pandang buruk pada tikungan, bangunan dekat dengan jalan, 800 m dari simpang terdapat jembatan rangka, kepala jembatan hanya 20 m dari tikungan, adanya jalan masuk ke desa, spanduk yang menarik perhatian dan mengganggu konsentrasi pengendara, parkir kendaraan sembarangan. Penelitian ini diharapkan dapat memberikan informasi tentang lokasi titik rawan kecelakaan untuk mengurangi resiko kecelakaan.Kata kunci : lalu lintas, kecelakaan, geometrik, tikungan, black spot